2016
DOI: 10.1177/1753193416660045
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and complications following surgery for Dupuytren’s disease: a multi-centre cross-sectional study

Abstract: Variables associated with recurrent Dupuytren's disease, or a 'diathesis', have been investigated, but those associated with functional outcome and complications are less well studied. Outcomes 1 or 5 years after an aponeurotomy, fasciectomy or dermofasciectomy were assessed by patient interview and examination at five UK centres. A total of 432 procedures were studied. The reoperation rate did not differ at 1 year (p = 0.396, Chisquare test with Monte Carlo simulation), but was higher after aponeurotomy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Eckerdal et al. (2014) and Rodrigues et al. (2017) additionally reported the proportion of patients achieving certain score thresholds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eckerdal et al. (2014) and Rodrigues et al. (2017) additionally reported the proportion of patients achieving certain score thresholds.…”
Section: Resultsmentioning
confidence: 99%
“…Complex regional pain syndrome was queried in 32 studies. The outcome was defined in three studies (Anwar et al., 2007; Rodrigues et al., 2017; Wade et al., 2016), and two of these (Rodrigues et al., 2017; Wade et al., 2016) used the standardized definition developed by the International Association for the Study of Pain (Harden et al., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In CTR the effect of age seems unclear as the results differ in different studies [22,25,27,30,31]. No effect of age has been found in studies on surgical treatment for DRF [23], surgical treatment for Dupuytren's Contracture [32], and open dorsal wrist ganglion excision [28] which makes it hard to determine whether or not age at the time of operation has an effect on hand surgical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed advantage of these techniques is reduced risk of recurrence as compared with minimally invasive procedures such as PNF, together with better correction of flexion deformity 65, 69, 71 . A potential benefit of dermofasciectomy is more radical clearance of the diseased tissue as well as potential myofibroblast precursors in the overlying fat and dermis, and a multi-centre cross-sectional study reported the reoperation rate following fasciectomy as 6% compared with 0% after dermofasciectomy at 5 years 72 . However, residual impairment of hand function did not differ between procedures, even when reoperation and other variables were controlled.…”
Section: Emerging and Existing Treatments For Dupuytren’s Diseasementioning
confidence: 99%